The 2018 ISDE achalasia guidelines. Issue 9 (30th August 2018) - Zaninotto, G; Bennett, C; Boeckxstaens, G; Costantini, M; Ferguson, M K; Pandolfino, J E; Patti, M G; Ribeiro, U; Richter, J; Swanstrom, L; Tack, J; Triadafilopoulos, G; et al.
Summary: Achalasia is a relatively rare primary motor esophageal disorder, characterized by absence of relaxations of the lower esophageal sphincter and of peristalsis along the esophageal body. As a result, patients typically present with dysphagia, regurgitation and occasionally chest pain, pulmonary complication and malnutrition. New diagnostic methodologies and therapeutic techniques have been recently added to the armamentarium for treating achalasia. With the aim to offer clinicians and patients an up-to-date framework for making informed decisions on the management of this disease, the International Society for Diseases of the Esophagus Guidelines proposed and endorsed the Esophageal Achalasia Guidelines (I-GOAL). The guidelines were prepared according the Appraisal of Guidelines for Research and Evaluation (AGREE-REX) tool, accredited for guideline production by NICE UK. A systematic literature search was performed and the quality of evidence and the strength of recommendations were graded according to the Grading of Recommendations Assessment, Development and Evaluation (GRADE). Given the relative rarity of this disease and the paucity of high-level evidence in the literature, this process was integrated with a three-step process of anonymous voting on each statement (DELPHI). Only statements with an approval rate >80% were accepted in the guidelines. Fifty-one experts from 11 countries and 3 representatives from patient support associations participated to the preparations of the guidelines. These guidelines deal specifically with the following achalasia issues: Diagnostic workup, Definition of the disease, Severity of presentation, Medical treatment, Botulinum Toxin injection, Pneumatic dilatation, POEM, Other endoscopic treatments, Laparoscopic myotomy, Definition of recurrence, Follow up and risk of cancer, Management of end stage achalasia, Treatment options for failure, Achalasia in children, Achalasia secondary to Chagas' disease.